Understanding and Overcoming Barriers to Drink Counting. (6th December 2022) - Booth, Leon; Jongenelis, Michelle I.; Drane, Catherine; Brennan, Emily; Wakefield, Melanie; Chikritzhs, Tanya; Hasking, Penelope; Pettigrew, Simone
Abstract: Objectives: Drink counting has been found to be an effective protective behavioral strategy (PBS) to reduce alcohol consumption. However, little is known about attitudes to this strategy and barriers and facilitators to its use. The aim of this study was to explicate these factors and draw comparisons with less efficacious PBSs. Method : In Stage 1, 1, 703 Australian drinkers were surveyed about their perceptions of five PBSs ("Count the number of drinks you have, " "Drink slowly rather than gulping or sculling, " "Refuse an alcoholic drink you are offered because you don't really want it, " "Avoid trying to 'keep up' or 'outdrink' others, " and "Decide not to exceed a certain number of drinks"). Respondents reported perceived believability, relevance, ease of use, effectiveness, barriers, and facilitators. In Stage 2, 10 focus groups were conducted with drinkers to identify potential methods of effectively promoting drink counting. Results : Overall, drink counting was rated less favorably than the less-efficacious PBSs, indicating a need to inform drinkers of the importance and feasibility of this strategy to encourage its use. The main identified barriers were a lack of awareness of the long-term harms associated with alcohol use, social factors (e.g., peer pressure), and difficulty counting when intoxicated. Participants suggested improving drinkers' understanding of alcohol-related harms and developing mechanisms to assist with counting. Conclusion : To encourage drink counting, information campaigns are needed to educate the community about the long-term risks of alcohol use. Evidenced-based mechanisms to facilitate drink counting may be welcomed by drinkers.